INVESTIGATING FACTORS AFFECTING MILLENNIALS AND GEN Z DECISION MAKING ON USING E-WALLET IN INDONESIA - Antasyah Akbar, Aqshal Haikal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Nowadays, the Indonesian people cannot deny that financial technology, especially the existence of a digital wallet (e-wallet), can make it easier and create convenience for those who use it. This research aims to find out the relationship between Indonesia's citizens, especially the millennial generation and some of the Generation Z, and their decisions to use the e-wallet. There were 220 respondents of Millennials and Gen Z who are studying at universities throughout East Java. Some factors chosen by the researchers are; perceived ease of use, promotion given by the application companies, and advertisements that the company made, and perceived usefulness from the e-wallet application. By using the partial least squares structural equation modeling (PLS-SEM) method, the results show that perceived ease of use, promotions given by application companies, advertisements made by companies, and the perceived usefulness of e-wallet applications have an effect on decision making of respondents to use the e-wallet.Â Key words: E-wallet, Financial Technology, PLS-SEM, Perceived ease of use, Promotion and ads, Perceived of usefulness, Indonesia